Model Pembelajaran Kooperatif Jigsaw untuk Meningkatkan Keaktifan dan Hasil Belajar Siswa MTs Kelas VIII - Qisthi Fariyani (Jurnal Penelitian Pembelajaran Fisika, 2019)
The objective of this research is to test the effectiveness of Jigsaw learning model for increase activeness and learning outcomes. Sample used is students of MTs Darul Hasanah Semarang grade VIII. The design research is Pretest-Posttest Control Group Design. The method to collect data is documentation, observation, and test. Instrument used is test to measure scores of learning outcomes and observation sheet to measure scores of activeness. Based on significance test which significance level of 5% found tcalculate=1,951 for activeness of the students and for outcomes of the students found tcalculate=4,194. The result of t test higher than ttable=1,671. Based on the result, it can be concluded that Jigsaw cooperative learning be able to increase the activeness and learning outcomes of the students